Faster acquisition of conditioned fear to fear-relevant than to nonfear-relevant conditional stimuli - Ho, Y.; Lipp, Ottmar (Wiley-Blackwell Publishing, Inc., 2014)
Prepared learning theory posits that prepared associations are acquired rapidly and resist extinction. Although it has been shown repeatedly that prepared associations resist extinction, there is currently little evidence to support the proposal of faster acquisition. The current study provides such evidence using a within-subjects conditioning procedure with a 50% reinforcement schedule. Participants were presented with pictures of four animals, two fear-relevant (snake, spider) and two nonfear-relevant (fish, bird), one of each paired with an unpleasant electrotactile stimulus on 50% of the trials during acquisition. Differential electrodermal responding was observed within the first two blocks of acquisition for fear relevant but not for nonfear-relevant conditional stimuli, confirming the prediction that prepared associations are acquired faster than nonprepared associations.